People-centeredness in the context of sustainable development of the country: Issues of cultural policy and ensuring intellectual security - Kotsur, Vitalii; Bobina, Oleg; Shapovalova, Iryna; Vorchakova, Iryna; Sugatska, Nataliia (Edelweiss Applied Science and Technology, 2024)
The study attempts to comprehend today notion and paradigm of people-centeredness (anthropocentrism), which shaped today due to the emergence and rapid evolution of sustainable development paradigm, changing all spheres of humanity life. It is shown, in particular, that new anthropocentrism implies new cultural policy, based on intellectual capital protected by intellectual security, gaining increasingly important role.